From invisibility to visibility: a policy archaeology of the introduction of anti-transphobic and anti-homophobic bullying guidelines into the Irish primary education system. Issue 1 (2nd January 2017) - Bailey, Susan
Abstract : In September 2013, the Department of Education and Skills introduced revised anti-bullying guidelines which made it compulsory for all schools to ensure that their individual anti-bullying policies include a clause on identity-based bullying, specifically referencing transphobic and homophobic bullying. The introduction of these guidelines would appear to represent an anomaly within the context of the Irish primary education system, which is 96% denominational. This paper considers the possibilities of the co-existence of guidelines which aim to counter homophobic and transphobic bullying and a school ethos which views homosexuality and transsexuality as sinful. Employing Scheurich's policy archaeology methodology, this paper presents some of the discursive practices which were at play in permitting the bullying of lesbian, gay, bisexual, and transgender children to emerge as an educational problem for which the revised anti-bullying guidelines were constructed as the policy solution.